Research of Technology of Deodoration of Sunflower and Cotton Oil and Their Analysis - Sattorova Barnokhon Nabiyevna; Musayeva Sarvinoz Shermuhammad qizi (Zien Journals, 2022)
In this article, I have summarized my findings on the quality indicators, analysis, and changes identified in the process of deodorizing sunflower and cottonseed oil in the course of my research. Experiments have shown that deodorized oils are safe to eat, and that they are different from non-deodorized oils. In order to ensure food safety, special attention is paid to scientific research on the modernization of production technology using deodorized oils. The main goal is to improve the performance of deodorized oils in the world, reduce material and technological costs for their production, optimize the technological conditions of production, ensure the quality of consumer products and food safety.
Keywords: cottonseed oil; sunflower oil; deodorization technology; refractive index